Створення власного уявлення для Android додатків - Гречмак, Д. В.; Гунько, М. А. (ХНУРЕ, 2021)
Android offers a sophisticated and powerful componentized model for building your UI, based on the fundamental layout classes: View and ViewGroup. To start with, the platform includes a variety of prebuilt View and ViewGroup subclasses – called widgets and layouts, respectively – that you can use to construct your UI. Creating your own View subclasses gives you precise control over the appearance and function of a screen element. To give an idea of the control you get with custom views.
Keywords: Android; Application; UI